Systematic study of magnetar-powered hydrogen-rich supernovae - Orellana, Mariana Dominga (2018)
Context. It has been suggested that some supernovae (SNe) may be powered by a magnetar formed at the moment of the explosion. While this scenario has mostly been applied to hydrogen-free events, it may also be possible for hydrogen-rich objects. Aims. We aim to explore the effect of including a magnetar on the light curves of supernovae with H-rich progenitors. Methods. We have applied a version of our one-dimensional local thermodynamic equilibrium radiation hydrodynamics code that takes into account the relativistic motion of the ejecta caused by the extra energy provided by the magnetar. For a fixed red supergiant (RSG) progenitor, we have obtained a set of light curves that corresponds to different values of the magnetar initial rotation energy and the spin-down timescale. The model is applied to SN 2004em and OGLE-2014-SN-073, two peculiar Type II SNe with long-rising SN 1987A-like light curves, although with much larger luminosities. Results. The presence of a plateau phase in either normal or superluminous supernovae is one possible outcome, even if a magnetar is continuously injecting energy into the ejecta. In other cases, the light curve shows a peak but not a plateau. Also, there are intermediate events with a first peak followed by a slow decline and a late break of the declining slope. Our models show that bright and long rising morphologies are possible even assuming RSG structures. Conclusions. A large number of supernova discoveries per year reveal unexpected new types of explosions. According to our results, SLSNe II-P are to be expected, as well as a variety of light curve morphologies that can all be possible signs of a newly born magnetar.